Reproductive health service use and associated factors among youths in Becho district, southwest Ethiopia - Waga, Teshome Tolosa; Shuremu, Muluneh; Zewdie, Asrat; Kera, Abeza Mitiku; Degefa, Gutama Haile (Frontiers in Public Health, 2023)
Background: Young people are less informed, less experienced, and less at ease when it comes to accessing reproductive health services than adults. Though youth-friendly services are designed to accommodate the unique needs of youth, in developing countries like Ethiopia, studies on the level of utilization of reproductive health services are limited. Objectives: This study determined the level of reproductive health (RH) service use and associated factors among youths. Methods: A community-based cross-sectional study was conducted in Becho district, Iluababor zone, southwest Ethiopia. A random selection of youths was undertaken, and data on socio-demographic characteristics, sexual and reproductive health characteristics, knowledge, and components of RH assessment were assessed. Results: More than half of the study participants were male. Reproductive health (RH) services were utilized by 43.9% of youths. Knowledge of RH services, discussion with family, a history of sexual exposure, distance from a health facility, and facing reproductive health problems were factors associated with RH service utilization. Conclusion: The use of reproductive health services among youths is found to be low. Knowledge about reproductive health services, discussion with parents, sexual exposure, distance, and previous experience with reproductive health problems shaped the utilization of RH services by youth. Improving knowledge through information dissemination, creating awareness to increase parent-child intimacy, and expanding health services should be emphasized.